Living up to one's word? Labor safeguarding in family firms during the Corona Crisis - Jeremiah Nollenberger (University of Duisburg-Essen, Institute for Socio-Economics (ifso), 2024)
The economic literature has remarked on the stability of the German labor market, despite the severe impact of the pandemic induced recession. So, what factors contributed to this stability? The literature stresses the use of internal flexibility on firm level - reducing working hours and productivity - as key to understand safeguarding of employment. This use of internal flexibility was, in addition, strongly aided by state policies, such as short-time work. In complementarity to these arguments, the family business literature contends that family firms offer higher job security from economic shocks (implicit labor contracts). Family corporate governance is thus argued to lead to more extensive use of internal flexibility measures. To assess this argument, we analyze the German Bundesbank-Online-Panel-Firms survey (BOP-F). The data show that family firms did indeed offer higher job security. The propensity-score-matched regression estimates show family firms reacted around 50-60% less to changes in sales in terms of employment than their nonfamily firm counterparts. Looking at the use of financial instruments and government support programs, we find that family firms were more likely to use private financial instruments, such as retained earnings and private loans, whereas they were just as likely to receive government aid. Zooming out, these findings speak to family firms playing a pivotal role in preserving highly asset-specific labor market matches in times of crisis deemed essential for coordinated market economies. They do this by managing private capital differently, while not showing greater independence from the state as commonly conceived.
Keywords: D22; G32; J21; J50; M51; 330; family firms; implicit labor contracts; Corona Crisis; employment